BRANDING IN THE DEVELOPMENT OF MATARAM ANCIENT KINGDOM TOURISM VILLAGE IN PLERET KELURAHAN BANTUL, YOGYAKARTA SPECIAL REGION - Itok Dwi Kurniawan; Lia Lestari; Muhammad Yusuf Airlangga (LP2M STP Mataram, 2022)
The development of tourist villages is one of the efforts to improve the local community's economy. The development of the potential possessed by the village is one way out that can be offered. Pleret Village, which is located in Pleret District, Bantul Regency, Special Region of Yogyakarta, has various potentials that can be developed. Especially in the field of tourism. The development of tourism potential owned by Pleret is still in the development and revitalization stage. The tourism village branding activities carried out by the 2021 UNS KKN TIM include making profile videos, tourism village logos, and publications on social media. This branding activity is carried out to introduce or promote the potential of Pleret village, especially in the field of tourism to a wide audience. The more recognition of the potential possessed by the village of Pleret will later bring in domestic tourists and will increase the economic lift of the surrounding community who had been affected by the pandemic. Tourism village branding carried out by the 2021 UNS KKN TEAM in collaboration with various parties who participated in helping the smooth running of the program. The expected output is being able to raise the tourism potential of Pleret village, helping to increase MSMEs around tourist destinations, fiber being able to provide a new perspective where the digital world has a very effective and efficient role in various fields, especially in this case tourism village marketing.